Stumpless chronic total occlusion with no retrograde option: Multidetector Computed Tomography‐Guided Intervention via Bi‐Radial Approach Utilizing Bioresorbable Vascular Scaffold. Issue 6 (22nd May 2015) - Dautov, Rustem; Abdul Jawad Altisent, Omar; Rinfret, Stéphane
Abstract : When dealing with flush ostial chronic total occlusion (CTO) and no viable retrograde option, the only way to perform recanalization is through an antegrade approach. Such a procedure can be extremely difficult considering the ambiguity of the proximal cap. We demonstrate how we solved ambiguity of the proximal cap of an ostial obtuse marginal CTO with the help of cardiac multidetector computed tomography (MDCT). We also discuss several techniques including bilateral radial approach with home‐made sheathless large‐bore catheters, IVUS‐guided cap puncture, ping‐pong guide catheters engagement in the left main, and bioresorbable vascular scaffold (BVS) for an ostial left circumflex disease that we all used in our CTO case. © 2015 Wiley Periodicals, Inc.